亚院二年级学生使用方位词“里”与“中”的偏误分析 KESALAHAN PENGGUNAAN KATA BENDA PENUNJUK ARAH “LI” DAN “ZHONG” PADA MAHASISWA STBA-PIA SEMESTER IV T.A. 2018/2019 - Dewi Kartika; Weni Maherna (Journal of Language, Literature and Teaching, 2022)
This study aims to describe the types of errors and the factors that cause errors in the use of directional nouns “li” and “zhong” made by STBA-PIA students in the fourth semester of academic year 2018/2019. The research method used is descriptive qualitative, namely to describe the types of errors and the factors of errors. The instruments used in this research are elicitation techniques and interview techniques. The research subject was taken using snowball sampling techniques, which was as many as 25 subjects. The results of the research conducted by research on STBA-PIA students in fourth semester of academic year 2018/2019 are 10 omission errors, 6 addition errors, 14 misformations and 3 misordering. Meanwhile, the factors that cause errors are namely interlingual errors, which are 7 respondents and intralingual errors, which are 15 respondents.Keywords: Language Errors, Directional Nouns, “li”, and “zhong”